Macroeconomic policy effectiveness and inequality: Efficacy of gender budgeting in Asia Pacific - Lekha Chakraborty; Marian Ingrams; Yadawendra Singh (Levy Economics Institute of Bard College, 2019)
Gender budgeting is a fiscal approach that seeks to use a country's national and/or local budget(s) to reduce inequality and promote economic growth and equitable development. While the literature has explored the connection between reducing gender inequality and achieving growth and equitable development, more empirical analysis is needed on whether gender budgeting reduces gender inequality. Our study follows the methodology of Stotsky and Zaman (2016) to investigate the impact of gender budgeting on promoting gender equality across Asia Pacific countries. The study classifies Asia Pacific countries as gender budgeting or non-gender budgeting according to whether they have formalized gender budgeting initiatives in laws and/or budget call circulars. To measure the effect of gender budgeting on reducing inequality, we measure the correlation between gender budgeting and the Gender Development Index (GDI) and the Gender Inequality Index (GII) scores in each country. The data for our gender inequality variables are mainly drawn from the IMF database on gender indicators and the World Development Indicators database over the 1990-2013 period. Our results show that gender budgeting has a significant effect on increasing the GDI and a small but significant potential to reduce the GII, strengthening the rationale for employing gender budgeting to promote inclusive development. However, our empirical results show no prioritization of gender budgeting in the fiscal space of health and education sectors in the region.
Keywords: H00; I3; J1; 330; Gender Budgeting; Fiscal Policy; Gender Equality; Asia Pacific